Outage Analysis of Transmit Beamforming and Relay Selection with Outdated Channel Estimates over Nakagami- Fading Channels - Lei Wang; Yueming Cai; Liang Zhang; Weiwei Yang (International Journal of Distributed Sensor Networks)
We investigate the joint effects of feedback delay and channel estimation errors (CEE) over Nakagami- m fading channels for two-hop amplify-and-forward (AF) relaying systems with transmit beamforming (TB) and relay selection (RS). We derive new closed-form expressions for the system outage performance including the exact analysis and informative high SNR asymptotic approximations, which indicate that TB feedback delay reduces the achievable diversity order to one, regardless of Nakagami- m fading parameters. Whereas RS delay reduces the diversity order to a case without relay selection and CEE merely result in coding gain loss, numerical results verify the theoretical analysis and illustrate that the outage performance is more sensitive to the TB feedback delay.